Criança no lugar de criança: territorialidades infantis no noroeste fluminense - Vasconcellos, Tania de (2008)
The result of a qualitative investigation based on anecdotes of teachers of up to six-year-old children from Santo Antônio de Pádua, Northwestern Rio de Janeiro, this work presents childhood and space as cultural and historical constructs; products of social relationships. Thus, the production of the place and the production of childhood are connected concepts; that is to say, every child is a child from a place and, at the same time, it has a place in the structure of the social group to which it belongs. The impossibility of giving up the place category in studies aiming at discussing childhood in its materiality, in handling everyday life, forces us to think of both as categories in permanent and implicated construction consequently, as a political task. The study of childhood, from this point of view, is always the study of the territorialities that limit it. This work calls infancy territorialities this field of conflicts and negotiations in which adults, children and institutions move and in which, in the articulation of the existing tensions, give a new face to the territory. It is a dynamic, permanent and unfinished process hereby symbolized by the metaphor of the dialogue between the old and wise narrator, the representative of experience, and the young infantile barbarian, responsible for the irruption of the novelty.